2022
DOI: 10.17219/dmp/150615
|View full text |Cite
|
Sign up to set email alerts
|

Can sleeping habits be associated with sleep bruxism, temporomandibular disorders and dental caries among children?

Abstract: Background. Sleeping problems are common in the pediatric population. Their potential relationship with oral manifestations is in the scope of researchers' interest.Objectives. The aim of the present study was to evaluate the possible associations between sleeping habits and sleep bruxism, temporomandibular disorders (TMD) and dental caries among children by using Children's Sleep Habits Questionnaire (CSHQ). Material and methods.A cross-sectional study was carried out at the Faculty of Dentistry of Istanbul A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 30 publications
1
25
0
Order By: Relevance
“…The underlying mechanisms of sleep include the modulation of inflammatory immune mechanisms. Sleep disorders can be categorized as insomnia, sleep-related breathing disorders, and sleep–wake circadian rhythm disorders [ 61 ]. Sleep problems in childhood can affect the child’s health and development [ 62 ].…”
Section: Sleep Homeostasismentioning
confidence: 99%
See 2 more Smart Citations
“…The underlying mechanisms of sleep include the modulation of inflammatory immune mechanisms. Sleep disorders can be categorized as insomnia, sleep-related breathing disorders, and sleep–wake circadian rhythm disorders [ 61 ]. Sleep problems in childhood can affect the child’s health and development [ 62 ].…”
Section: Sleep Homeostasismentioning
confidence: 99%
“…Studies have shown that individuals who go to bed later at night risk developing dental caries more than those who go earlier [ 70 ]. In addition, later going to bed [ 9 , 61 ] and short night sleep duration are associated with an increased risk of caries [ 50 ]. In children, the sleeping routine is also essential, and those children who had an irregular bedtime had a higher prevalence of caries [ 50 ].…”
Section: Sleep Homeostasismentioning
confidence: 99%
See 1 more Smart Citation
“…TMDs are often associated with biomechanical issues such as malocclusion, in which the teeth are not properly aligned when the jaws are closed. TMD can also be caused by bruxism (long-term teeth grinding or clenching) and abnormal jaw growth patterns in children [2]. Sleep bruxism is commonly characterized by rhythmic or non-rhythmic grinding or clenching of the teeth while asleep [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…TMD can also be caused by bruxism (long-term teeth grinding or clenching) and abnormal jaw growth patterns in children [2]. Sleep bruxism is commonly characterized by rhythmic or non-rhythmic grinding or clenching of the teeth while asleep [2,3]. In otherwise healthy individuals, it is not considered a disorder but may be a risk factor for negative oral health consequences like TMD [4][5][6].…”
Section: Introductionmentioning
confidence: 99%